Success factors of global virtual teamwork: A social capital perspective - Tim Heubeck; Anne-Sophie Storz; Reinhard Meckl (Digital Business, 2024)
Global virtual teamwork has emerged as a cornerstone of collaborative teamwork in today's work landscape, characterized by cross-border collaboration using digital technologies. Although research has started to investigate the mechanisms underlying effective teamwork through information and communication technologies (ICTs), an often-neglected dimension is the pivotal social context within which this collaboration unfolds. To address this research gap, this study adopts a social capital lens on teamwork in proposing social capital as a multidimensional mediator between the usage of ICTs and team effectiveness. The research model was tested using questionnaire data from 271 technologically sensitive and aware companies in the DACH region (Germany, Austria, Switzerland). The findings reveal that using multiple ICTs alone does not suffice for effective global virtual teamwork. Therefore, this study highlights the significance of social capital for the effectiveness of global virtual teamwork, which holds significant implications for theory and practice.
Keywords: 650; Global virtual teamwork; Information and communication technologies; Social capital; Team effectiveness